La gran causa nuestra. Unity and Literary Modernism in Central America - Rojas González, Margarita (2020)
This article is an inquiry about the relationship between modernist literature and the search for Central American unity, at the end of the 19th century. Rubén Darío was the key figure that guided the generation; his writing concretized the political idea of ​​unity through the notion of universal harmony. Other Central American writers such as Francisco Gavidia, Máximo Soto Hall, and Alberto Masferrer also published novels, poems, stories and essays on the subject in Costa Rica. This is the first partial result of an investigation about the literary elaborations of the concept of the Central American union.